Variability in the Drug Response of M4 Muscarinic Receptor Knockout Mice During Day and Night Time - Valuskova, Paulina; Riljak, Vladimir; Forczek, Sandor T.; Farar, Vladimir; Myslivecek, Jaromir (Frontiers in Pharmacology, 2019)
Mice are nocturnal animals. Surprisingly, the majority of physiological/pharmacological studies are performed in the morning, i.e., in the non-active phase of their diurnal cycle. We have shown recently that female (not male) mice lacking the M4 muscarinic receptors (MR, M4KO) did not differ substantially in locomotor activity from their wild-type counterparts (C57Bl/6Tac) during the inactive period. Increased locomotion has been shown in the active phase of their diurnal cycle. We compared the effects of scopolamine, oxotremorine, and cocaine on locomotor response, hypothermia and spontaneous behavior in the open field arena in the morning (9:00 AM) and in the evening (9:00 PM) in WT and in C57Bl/6NTac mice lacking the M4 MR. Furthermore, we also studied morning vs. evening densities of muscarinic, GABAA, D1-like, D2-like, NMDA and kainate receptors using autoradiography in the motor, somatosensory and visual cortex and in the striatum, thalamus, hippocampus, pons, and medulla oblongata. At 9:00 AM, scopolamine induced an increase in motor activity in WT and in M4KO, yet no significant increase was observed at 9:00 PM. Oxotremorine induced hypothermic effects in both WT and M4KO. Hypothermic effects were more evident in WT than in M4KO. Hypothermia in both cases was more pronounced at 9:00 AM than at 9:00 PM. Cocaine increased motor activity when compared to saline. There was no difference in behavior in the open field between WT and M4KO when tested at 9:00 AM; however, at 9:00 PM, activity of M4KO was doubled in comparison to that of WT. Both WT and KO animals spent less time climbing in their active phase. Autoradiography revealed no significant morning vs. evening difference. Altogether, our results indicate the necessity of comparing morning vs. evening drug effects